2017
DOI: 10.1038/cti.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from ten years of genome‐wide association studies of asthma

Abstract: Twenty-five genome-wide association studies (GWAS) of asthma were published between 2007 and 2016, the largest with a sample size of 157242 individuals. Across these studies, 39 genetic variants in low linkage disequilibrium (LD) with each other were reported to associate with disease risk at a significance threshold of P<5 × 10−8, including 31 in populations of European ancestry. Results from analyses of the UK Biobank data (n=380 503) indicate that at least 28 of the 31 associations reported in Europeans rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 133 publications
7
109
0
Order By: Relevance
“…In parallel, we found that the rs2228145:C allele was associated with a 1.09-fold higher risk of asthma in individuals of European descent, 66 an observation that has since been replicated in the UK Biobank study. 64,67 A similar association (odds ratio [OR] = 1.08) was also reported for atopic dermatitis (AD or eczema), 68 with a stronger effect (OR = 1.22) observed for the persistent form of AD. 69 Recently, we showed that rs2228145:C occurs at the same frequency in cases that suffer from asthma, hay fever or AD, therefore confirming its effect on the risk of multiple allergic diseases.…”
Section: Introductionsupporting
confidence: 53%
“…In parallel, we found that the rs2228145:C allele was associated with a 1.09-fold higher risk of asthma in individuals of European descent, 66 an observation that has since been replicated in the UK Biobank study. 64,67 A similar association (odds ratio [OR] = 1.08) was also reported for atopic dermatitis (AD or eczema), 68 with a stronger effect (OR = 1.22) observed for the persistent form of AD. 69 Recently, we showed that rs2228145:C occurs at the same frequency in cases that suffer from asthma, hay fever or AD, therefore confirming its effect on the risk of multiple allergic diseases.…”
Section: Introductionsupporting
confidence: 53%
“…variants associated with childhood asthma in large-scale GWA studies only account for a low fraction of variance in asthma severity, endotypes, heritability and clinical response to therapy. [5][6][7][8] Environmental exposures, such as tobacco smoke exposure during pregnancy, lack of breastfeeding and air pollutants that affect lung development and risk of asthma may alter gene activity and expression without changing underlying DNA sequence, referred to by the term epigenetics. [8][9][10] The genetic make-up of an individual and its interaction with the environment can both affect epigenetic mechanisms.…”
mentioning
confidence: 99%
“…Variants identified through GWAS only account for a small percentage of the heritability with the known lung function signals accounting for 9.6%, 6.4% and 14.3% of the heritability for FEV 1 , FVC and FEV 1 /FVC, respectively . In asthma, 2.5% of heritability is estimated to be due to SNP discovered through GWAS . This missing heritability is often attributed to the limitations of GWAS and it is a fact that GWAS only detect common variants and ignore other types of genomic variation such as rare variants and copy number variations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SNP spanning IL1RL1 , the IL‐33 receptor, are associated with childhood asthma, severe asthma and with a diagnosis of allergic rhinitis . For an excellent review of GWAS in asthma up until 2016, see the study by Vicente et al …”
Section: Methods For Studying Genetics Of Respiratory Diseasementioning
confidence: 99%
See 1 more Smart Citation